Sosialisasi Safety Road Berkendaraan Roda Dua pada Pelajar SMU/SMK di Balikpapan - Rahmat Rahmat; Irna Hendriyani; Gunaedy Utomo (Abdimas Universal, 2020)
The Director General of Traffic of the East Kalimantan Regional Police (2019) stated that, victims of traffic accidents 37% were 16-25 years old. The number of victims of accidents based on education is highest among students of Public High Schools and Vocational High Schools. Based on these facts, it is necessary to carry out activities aimed at broadening students' knowledge about Safety Road in two-wheeled vehicles and fostering awareness of driving that prioritizes road user safety. This activity was carried out in 3 sessions, namely giving pre-tests regarding traffic safety knowledge, the second session giving knowledge about traffic safety and question and answer, and ending with giving a post-test. Based on the test results found that an increase in the number of correct answers from the post-test and pre-test around 50%. From the results of the questionnaire, it was found that the implementation of this activity was very important and beneficial for the participants of the socialization.